2002
DOI: 10.1002/ana.10416
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortex excitability in Alzheimer's disease: A transcranial magnetic stimulation study

Abstract: Motor deficits affect patients with Alzheimer's disease only at later stages. Recent studies demonstrate that the primary motor cortex is affected by neuronal degeneration accompanied by the formation of amyloid plaques and neurofibrillary tangles. It is conceivable that neuronal loss is compensated by reorganization of the neural circuitries occurring along the natural course of the disease, thereby maintaining motor performances in daily living. Cortical motor output to upper limbs was tested via motor-evoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
133
2
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 204 publications
(152 citation statements)
references
References 46 publications
16
133
2
1
Order By: Relevance
“…This possible explanation is in line with previous evidence of abnormal central EEG rhythms or evoked potentials in AD subjects performing voluntary movements or perceiving somatosensory stimuli (Babiloni et al, 2000;Ferri et al, 1996). Furthermore, abnormally hyperexcitable primary motor cortex has been recently reported in AD, as revealed by EEG rhythms related to self-paced movements and transcranial magnetic stimulation (Babiloni et al, 2000;Pennisi et al, 2002;Ferreri et al, 2003;).…”
Section: Relative Power and Frequency Of Alpha Rhythms In Mild Dementiasupporting
confidence: 89%
“…This possible explanation is in line with previous evidence of abnormal central EEG rhythms or evoked potentials in AD subjects performing voluntary movements or perceiving somatosensory stimuli (Babiloni et al, 2000;Ferri et al, 1996). Furthermore, abnormally hyperexcitable primary motor cortex has been recently reported in AD, as revealed by EEG rhythms related to self-paced movements and transcranial magnetic stimulation (Babiloni et al, 2000;Pennisi et al, 2002;Ferreri et al, 2003;).…”
Section: Relative Power and Frequency Of Alpha Rhythms In Mild Dementiasupporting
confidence: 89%
“…Recent postmortem data from subjects -who had been prospectively followed and clinically characterized up to immediately before their death -indicate that hippocampal choline acetyltransferase levels are reduced in Alzheimer's dementia, but in fact they are upregulated in MCI (Lavenex and Amaral, 2000;DeKosky et al, 2002), presumably because of reactive upregulations of the enzyme activity in the unaffected hippocampal cholinergic axons. Previous EEG studies (Babiloni et al, 2000;Jelic et al, 2000Jelic et al, , 1996Ferreri et al, 2003) have shown a decrease -ranging from 8 to 10.5 Hz (low alpha) -of the alpha frequency power band in MCI subjects, when compared to normal elderly controls (Zappoli et al, 1995;Huang et al, 2000;Jelic et al, 2000;Koenig et al, 2005;Babiloni et al, 2006a). However, a recent study has shown an increase -ranging from 10.5 to 13 Hz (high alpha) -of the alpha frequency power band, on the occipital region in MCI subjects, when compared to normal elderly and AD patients (Babiloni et al, 2006a).…”
Section: Introductionmentioning
confidence: 94%
“…In AD patients, motor cortex excitability is increased (Ferreri et al, 2003). Extracellular A␤ enhances release probability at hippocampal synapses, increasing neuron network activity in vitro (Abramov et al, 2009).…”
Section: Introductionmentioning
confidence: 99%